Multi-model GWAS reveals genetic determinants of grain hardness, size and weight in bread wheat (Triticum aestivum L.) - Deepa Bhadana; Jitendra Kumar; Shoeb Ahmed; Anita Kumari; Monika Garg; Joy Roy; Rahul Kumar (Molecular Genetics and Genomics, 2026)

Development of an in-situ forming implant system for levodopa and carbidopa for the treatment of parkinson’s disease - Deepa D. Nakmode; Sadikalmahdi Abdella; Yunmei Song; Sanjay Garg (Drug Delivery and Translational Research, 2025)
Long-acting injectables have gained attraction as a system for treating chronic conditions due to their increased efficacy, safety, and patient compliance. Currently, patients with Parkinsons need to administer oral medications multiple times a day which imposes the significant risk of non-compliance. This study aimed to design an in-situ implant-forming system for controlled delivery of levodopa and carbidopa for up to 1 week which will reduce the need for multiple dosing. The combination of poly-lactic-co-glycolic acid (PLGA 50:50 ) and Eudragit L-100 was used to prepare the implants and the formulation was optimized to achieve a controlled release over 7 days. The optimized formulation containing 26% PLGA and 6% Eudragit L 100 displayed a favorable release profile and injectability with low viscosity. The optimized formulation in vitro release study revealed an initial burst of 34.17% and 37.16% for levodopa and carbidopa in the first 24 h and about 92% and 81% release within 7 days. A good correlation was observed between the in-vitro drug release data and ex-vivo drug release with a correlation coefficient of 0.91 for levodopa and 0.90 for carbidopa. Viscosity analysis showed the Newtonian behavior of the formulation. Syringeability analysis of the formulation showed that the maximum force required for expelling the formulation was 32.98 ± 0.72 N using a 22 G needle. The in-vitro degradation studies revealed 81.89% weight loss of implant in 7 days. The prepared formulation was assessed for in-vivo performance using a convolution modeling technique using a convolve function in R software. The predicted AUC 0-∞ h for the in-situ forming implant was 26505.5 ng/ml with Cmax, 399.3 ng/ml, and Tmax 24 h assuming 100% bioavailability. The results justify that the prepared in-situ implant forming system can be a promising system for the delivery of levodopa and carbidopa for Parkinson’s patients.

Genetic resources for enhancing drought tolerance from National Genebank collection of linseed (Linum usitatissimum L.) in India - Vikender Kaur; Devendra K. Payasi; Rakesh Choudhary; Vishnu Kumar; Shashank K. Yadav; Devender Singh; Vinay Kumar; Balram Jat; Deepa Garg; Vishal Kumar Gupta; Sudhir Kumar; Viswanathan Chinnusamy; et al. (Plant and Soil, 2025)

Correction: Long-acting parenteral formulations of hydrophilic drugs, proteins, and peptide therapeutics: mechanisms, challenges, and therapeutic benefits with a focus on technologies - Deepa D. Nakmode; Baljinder Singh; Sadikalmahdi Abdella; Yunmei Song; Sanjay Garg (Drug Delivery and Translational Research, 2025)

Long-acting parenteral formulations of hydrophilic drugs, proteins, and peptide therapeutics: mechanisms, challenges, and therapeutic benefits with a focus on technologies - Deepa D. Nakmode; Baljinder Singh; Sadikalmahdi Abdella; Yunmei Song; Sanjay Garg (Drug Delivery and Translational Research, 2025)
Despite being the most widely prescribed formulation, oral formulations possess several limitations such as low adherence, low bioavailability, high toxicity (in the case of anticancer drugs), and multiple-time administration requirements. All these limitations can be overcome by long-acting injectables. Improved adherence, patient compliance, and reduced relapse have been observed with long-acting formulation which has increased the demand for long-acting injectables. Drugs or peptide molecules with oral bioavailability issues can be easily delivered by long-acting systems. This review comprehensively addresses the various technologies used to develop long-acting injections with a particular focus on hydrophilic drugs and large molecules as well as the factors affecting the choice of formulation strategy. This is the first review that discusses the possible technologies that can be used for developing long-acting formulations for hydrophilic molecules along with factors which will affect the choice of the technology. Furthermore, the mechanism of drug release as well as summaries of marketed formulations will be presented. This review also discusses the challenges associated with the manufacturing and scale-up of the long-acting injectables. Graphical abstract

Fabrication of HA Nano-crystal Reinforced PHAs based composites for orthopedic fracture-fixing accessories using sustainable resources - Preeti Tomer; Gireesh Kumar Shroti; Swati Mohapatra; Debashish Ghosh; Satish Jaiswal; Deepa Garg; Debrupa Lahiri; Navin Kumar; Om P. Khatri; Saugata Hazra (Environment, Development and Sustainability, 2023)

Myricetin: a potential plant-derived anticancer bioactive compound—an updated overview - Suneel Kumar; Nitin Swamy; Hardeep Singh Tuli; Seema Rani; Abhijeet Garg; Deepa Mishra; Hadi Sajid Abdulabbas; Sardul Singh Sandhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Hybrid gum tragacanth/sodium alginate hydrogel reinforced with silver nanotriangles for bacterial biofilm inhibition - Deepa Garg; Ishita Matai; Shruti Agrawal; Abhay Sachdev (Biofouling, 2022)

Neuroleptic malignant syndrome as a presenting feature of subacute sclerosing panencephalitis - Divyani Garg; Varun Reddy; Rajesh Kumar Singh; Deepa Dash; Rohit Bhatia; Manjari Tripathi (Journal of NeuroVirology, 2018)